Chytridiomycosis Outbreak in a Chilean Giant Frog (Calyptocephalella gayi) Captive Breeding Program: Genomic Characterization and Pathological Findings - Alvarado-Rybak, Mario; Acuña, Paz; Peñafiel-Ricaurte, Alexandra; Sewell, Thomas R.; O'Hanlon, Simon J.; Fisher, Matthew C.; Valenzuela-Sánchez, Andres; Cunningham, Andrew A.; Azat, Claudio (Frontiers in Veterinary Science, 2021)
Emerging infectious diseases in wildlife are increasingly associated with animal mortality and species declines, but their source and genetic characterization often remains elusive. Amphibian chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis (Bd), has been associated with catastrophic and well documented amphibian population declines and extinctions at the global scale. We used histology and whole-genome sequencing to describe the lesions caused by, and the genetic variability of, two Bd isolates obtained from a mass mortality event in a captive population of the threatened Chilean giant frog (Calyptocephalella gayi). This was the first time an association between Bd and high mortality had been detected in this charismatic and declining frog species. Pathological examinations revealed that 30 dead metamorphosed frogs presented agnathia and brachygnathia, a condition that is reported for the first time in association with chytridiomycosis. Phylogenomic analyses revealed that captive C. gayi isolates group with other isolates forming a single highly supported Chilean Bd clade within the global panzootic lineage of Bd (BdGPL). These findings are important to inform the strengthening of biosecurity measures to prevent the impacts of chytridiomycosis in captive breeding programs elsewhere.